Photo Degradation of p-Nitrophenol in Presence of Semiconductor - Joshi, J.D.; Vora, Jabali; Sharma, Sangita; C. Patel, Chirag; B. Patel, Ashok (Asian Journal of Chemistry, 2016)
The photocatalytic degradation of p-nitrophenol by irradiation in presence of semiconductor ZnO was studied. Kinetics of the reaction were found to be affected by parameters like concentration of substrate, pH, amount of photocatalyst, light intensity, band gap, etc. The effects of radical quencher, sensitizer were also studied. A probable mechanism is also suggested.